Pendampingan Peningkatan Publikasi Konten Digital Spritual Education Pada Sekolah Dasar Negeri Galak Slahung Ponorogo - Muhammad Sabilillah; Mochamad Hanif Ibnu Jatnika; Muhammad Tharmidzi; Ariya Supandi; Mohammad Luthfi (UM Metro, 2026)
The presence of digital media provides space for educational institutions to disseminate spiritual educational content to the community quickly and accurately. Various photo and video content of school activities can be published through various digital platforms. This Community Service was carried out at the State Elementary School of Galak Village, Slahung District, Ponorogo Regency, which aims to improve teacher skills in writing captions, photography and videography in order to optimize the school's spiritual educational content through digital media. The community service program is based on the results of observations and interviews with the principal which show that the use of school digital media has not been running optimally due to the low knowledge and skills of teachers in writing captions, photography and videography as a provision of skills in creating educational digital content. The implementation of the community service program through socialization and direct practice to train teachers as program participants in understanding and creating digital educational content. The results of the community service show a significant increase in the aspects of participants' understanding and skills in creating content and managing social media as an educational instrument. In addition, the school's previously inactive social media was then updated and reused to spread spiritual values in a creative and interesting way.